A nordic ski coach's learning journey towards creating more inclusive and safer sport - Kramers, S.; Carrier-Laforte, S.; Camiré, M. (International Sport Coaching Journal, 2025)
Competitive youth sport coaches who aim to foster inclusive and safer sport often face challenges from their peers, their organisations, and the sociocultural systems in their contexts. A personal learning coach may support coaches` critical awareness, reflection, and readiness for working towards changing their youth sport contexts. This study details a 15-month collaboration, as Sara acted as a personal learning coach to support Sophie`s critical praxis as they reflected on social issues and experienced shifts in their coaching towards creating more inclusive and safer sport. Grounded in a narrative inquiry methodology, two virtual interviews and 11 virtual meetings occurred. Sara and Sophie also shared reflections through messages and voice notes and one in-person meeting during one of Sophie`s training sessions. Through time-hopping snapshot vignettes, Sophie`s learning journey is presented as they attempt to figure out what to fight for, grow through discomforts and unknowns, and experience progress. Sophie believed that their "mind shifted" towards becoming a "better coach" throughout the collaboration, developing their critical consciousness to change oppressive social conditions in sport. By sharing insights from the collaboration, the study provides vivid examples of the steps coaches and sport stakeholders can take to become more confident in enacting positive change in sport.